Cognitive modulation of the cerebral processing of human oesophageal sensation using functional magnetic resonance imaging. Issue 12 (21st November 2003) - Gregory, L J; Yágüez, L; Williams, S C R; Altmann, C; Coen, S J; Ng, V; Brammer, M J; Thompson, D G; Aziz, Q
Abstract : Background: While cortical processing of visceral sensation has been described, the role that cognitive factors play in modulating this processing remains unclear. Aim: To investigate how selective and divided attention modulate the cerebral processing of oesophageal sensation. Methods: In seven healthy volunteers (six males, mean age 33 years; ranging from 24 to 41 years old) from the general community, phasic visual and oesophageal (non-painful balloon distension) stimuli were presented simultaneously. During the selective attention task, subjects were instructed to press a button either to a change in frequency of oesophageal or visual stimuli. During a divided attention task, subjects received simultaneous visual and oesophageal stimuli and were instructed to press a button in response to a change in frequency of both stimuli. Results: Selectively focussing attention on oesophageal stimuli activated the visceral sensory and cognitive neural networks (primary and secondary sensory cortices and anterior cingulate cortex respectively) while selective attention to visual stimuli primarily activated the visual cortex. When attention was divided between the two sensory modalities, more brain regions in the sensory and cognitive domains were utilised to process oesophageal stimuli in comparison to those employed to process visual stimuli (p = 0.003). Conclusion: Selective and divided attention to visceral stimuli recruits more neural resources in both the sensory and cognitive domains than attention to visual stimuli. We provide neurobiological evidence that demonstrates the biological importance placed on visceral sensations and demonstrate the influence of cognitive factors such as attention on the cerebral processing of visceral sensation.